Applications of readability findings in teaching languages - Diep, Nguyen Thi Nhu; Nam, Lam Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Readability or text readability, particularly in English, has been studied since the end of the 19th century with hundreds of thousands of published works. The research results on this issue are not only quite rich in resources but also universally applicable in many fields. Currently, it is an interesting problem and still being continuously studied by researchers, not only for English but also for many other languages. However, in Vietnam, the study of readability is still limited research to find the solutions to meet the social needs. Based on the findings and applicable results of readability studies, the paper, initially, presents an overview about readability and the linguistic factors having influence on readability. On the view from readability and applications, the paper investigates and analyses the linguistic factors on 3 main levels: Words, Sentences, and Texts by the illustrative case studies in English language, or Vietnamese language. On this basis, the paper suggests the practical applications of readability in teaching languages ​​in general, particularly in the context of teaching English in Vietnam currently, to meet the demand for users and Vietnamese community in the era of technology.